(3GdeSJbUi aj CeKGd GdYQHs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3GdaVd Hf CHj GdMSjf s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CKdL Hg UOhQfG ef HQO Gdjbjf s
(3BNQgG (B:s
(3jhgj hdG jQaY , jVQH def jaSO hdG jUdM s
(3GdfSNI HgG MhGTs
(3Ydi MhGTj GdfSNI ebGHdGJ hJYdjbGJ cJHJ GdCeKGd HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdCOHs